STUDI IN VITRO BAKTERI ASAM LAKTAT KANDIDAT PROBIOTIK DARI MAKANAN FERMENTASI INDONESIA - Gunawan Priadi; Fitri Setiyoningrum; Fifi Afiati; Rohmatussolihat Irzaldi; Puspita Lisdiyanti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Indonesia has a rich variety of fermented foods. The lactic acid bacteria contained in such fermented foods can act as probotics providing positive effects on digestive health. Lack of information about the characteristics of the native LAB caused insufficient use of them in functional food products. The purpose of this study was to carry out in vitro selection of potential probiotics of lactic acid bacteria isolated from non-dairy fermented foods i.e. pickle, cassava tape, terasi and dadih. The probiotic property tests are acid and bile salt tolerance assays, hydrophobicity test, adhesion test and coaggregation test. LAB isolates passing all tests indicate that they are potential as probiotics. This study obtained 4 LABs having probiotics properties by in vitro tests, i.e. L. plantarum LIPI12-2-LAB004 from pickle (Yogyakarta), L. plantarum LIPI12-2-LAB031 from cassava tape (Yogyakarta), L. plantarum LIPI13-2-LAB011 from terasi (Bali), and L. plantarum LIPI13-2-LAB087 from terasi (Solok). The four LAB were able to survive high acid and bile salt concentrations above 85%, had hydrophobicities above 95%, capable of adhering to solid surfaces for 24 hours, and were able to co-aggregate with other LAB isolates.